Knowledge, Acceptability, Perception and Stigmas on Safe Abortion among the women of reproductive age group (15-49 years) in Bhaktapur District. - Shrestha, Ankisha; Sinha, Ram Chandra; Ahmad, Aalia (Medical Journal of Shree Birendra Hospital, 2021)
Introduction: The termination of pregnancy by the removal of a foetus or an embryo before surviving outside the uterus or before attaining its viability is called abortion. This study was conducted to study the knowledge, acceptability, perception and stigma of safe abortion among women of reproductive age group. Methods: A cross-sectional analytical study was carried out in Bhaktapur District, Nepal from July 2019 to December 2019. Women of reproductive age group were included in the study. The semi-structured questionnaires were used as a data collection tool and Likert scales were used for perception and stigma which were self-designed. For Likert scale on perception and stigma, Cronbach’s α was calculated from the pre-tested samples which was found to be acceptable i.e., 0.649 and 0.856. Interview was taken as data collection technique. Data-entry was done in Epi-Data and analysed through SPSS 16.0. Chi square test was used to measure the association between dependent and independent variables. Result: The association between “Knowledge and Perception” was found to be significant with p-value of 0.04, the association between “Knowledge and Stigma” was also noted to be significant with p-value of 0.00 and “Knowledge and Acceptability” was also found to be significant with p-value of 0.00 through the assessment of knowledge, acceptability, perception and stigma. Conclusions: The study emphasises on educating and making aware every woman on safe abortion, its legalisation and its amended law to avoid the stigma and unsafe abortion practices.